Cobalt ferrate nanoparticles improved dark fermentation for hydrogen evolution. (20th September 2021) - Zhang, Jishi; Li, Wenqing; Yang, Junwei; Li, Zhenmin; Zhang, Junchu; Zhao, Wenqian; Zang, Lihua
Abstract: In this work, the cobalt ferrate nanoparticles were prepared by a sol-gel method for investigating their influence on hydrogen production from dark fermentation. A moderate amounts (0.1–0.4 g/L) of these nanoparticles effectively enhanced the fermentation process. The highest hydrogen yield of 205.24 mL/g glucose was achieved at a dosing level of 0.4 g/L, which was a 31.8% enhancement compared to the control, while excess (0.5 g/L) nanoparticles decreased the hydrogen production by 9.7% compared to the control group. The mechanism analysis exhibited that the nanoparticles could either attach to the microbial surface or enter the cell interior without destroying the cell integrity, which promoted the electron transfer to anaerobes and stimulated the activities of hydrogen-producing enzymes such as enzymes and coenzymes. The microbial community revealed that a moderate amount of cobalt ferrate nanoparticles increased the abundance of Clostridium sensu stricto 1 from 14.49% to 18.84%, which was dominant and favored the sustainable conversion of glucose wastewater into clean hydrogen. Graphical abstract: Image 1 Highlights: Cobalt ferrate nanoparticles (CoFe2 O4 NPs) were synthesized to increase H2 yield. BioH2 production was enhanced by 31.8% with 0.4 g/L CoFe2 O4 NPs. CoFe2 O4 NPs changed the type of fermentation to butyric acid fermentation. CoFe2 O4 NPs promoted microbial activity by acting on the microbial interface. CoFe2 O4 NPs improved the abundance of Clostridium_sensu_stricto_1.